Perancangan Sistem Informasi Pendaftaran Pasien Rawat Jalan Berbasis Web Di Puskesmas Pimping - Elicukia, Elicukia; Yunengsih, Yuyun (Akademi Perekam dan Informasi Kesehatan Imelda, 2025)
The registration process is a crucial element in medical record management, ensuring the smooth operation of healthcare services and impacting the quality of services. This study aims to design a web-based patient registration information system to improve the quality of healthcare services and operational efficiency in community health center. This research employs a qualitative method with a descriptive approach, where data is collected through direct observation, interviews with medical record officers, and literature review. The sample consisted of two medical record officers, and the research was conducted at Pimping Community Health Center (Puskesmas Pimping) on December 20, 2024. For system development, a prototype-based system development method was used. The results of the study reveal that community health centers still use a manual paper-based registration system, leading to recording errors and administrative inefficiencies. To address these issues, a web-based information system has been designed to reduce administrative burdens, improve data accuracy, and accelerate the patient registration process. The implementation of this system demonstrates improved operational efficiency, a reduction in registration errors, and ease for staff in managing patient data through an intuitive interface. As a recommendation, this system requires further testing in real-world settings to gather user feedback, enabling continuous improvements to its features to meet field requirements.